Early Lexical Development and the Development of Translation Equivalents in a Simultaneous Bilingual Child - Sri Adnyani, Ni Luh Putu; Sutjiati Beratha, Ni Luh; Pastika, I Wayan; Suparwa, I Nyoman (e-Journal of Linguistics; Vol 11 No 2 (2017): eJL-JulyDO - 10.24843/eJL.2017.v11.i02.p04, 2017)
This study focuses on the development of lexicon by a child raised simulatneously in Indonesian and German from birth. In the immediate family members, the child received Indonesian from the mother and German from the father. The data was collected in natural setting when the child was 1;0 up to 3;0. In collecting the data, diary records and weekly video recordings were used. The data was analized using two softwares, ELAN and Toolbox. The child’s speech was segmented based on the child’s utterances. The result of the study shows that at the end of the study the child developed 521 lexicon in Indonesian and 243 in German. Both in Indonesian and German the child acquired more nouns than verbs. Besides, the child also developed about 164 translation equivalents. Thus, it confirms that the bilingual child developed two different lexical systems.